Comment on ‘Practical advice for avoidance of pain associated with insertion of intrauterine contraceptives’ - Guillebaud, John (BMJ sexual & reproductive health, 2014)
With tolfenamic acid 200 mg three times a day started post-insertion, significantly reduced (p<0.01) spasmodic pain was reported in the subsequent 24 hours 4 ; and measured by visual analogue scales (VAS), there was significant post-insertion pain reduction at 10 minutes with mefenamic acid 500 mg given 60 minutes pre-insertion. 2 Moreover, the "absence of proof" from other good studies cited in the Cochrane Review 3 cannot be "proof of absence" of benefit by non-steroidal anti-inflammatory drugs (NSAIDS) for prostaglandin-related pain. Robinson et al. 5 reported in a double-blind randomised controlled trial that hysterosalpingography subjects receiving a 1% lidocaine cervical block totalling 6 ml had significantly less pain (p<0.001) measured by VAS from tenaculum placement, compared with a placebo intracervical saline injection group and a no-injection group.